Screening for dysphagia in patients with relapsing-remitting multiple sclerosis - Kocica, Jan; Lasotova, Nadezda; Kolcava, Jan; Svobodova, Monika; Hladikova, Magdalena; Stourac, Pavel; Bednařík, Josef; Vlckova, Eva (Multiple sclerosis and related disorders, 2024)
BACKGROUND: In multiple sclerosis (MS), dysphagia is an important and common clinical symptom. Although often overlooked and underdiagnosed, it can have a significant impact on a patient's life, including social integration, and it can lead to malnutrition, aspiration pneumonia, and suffocation, i.e., life-threatening complications. Early detection of dysphagia is essential to prevent these risks. However, the optimal screening method and the inter-relationship between different methods used for dysphagia screening are not clear. The aim of this study was to compare the diagnostic performance of a simple question about swallowing problems, the DYsphagia in MUltiple Sclerosis (DYMUS) swallowing questionnaire, and the Timed Water Swallowing Test (TWST) to detect dysphagia in people with relapsing-remitting MS (RRMS). METHODS: Patients with MS were asked about subjective swallowing difficulties and, regardless of their response, completed the DYMUS questionnaire and underwent the TWST at their routine follow-up visit. Patients with at least one positive screening method were offered an objective assessment of swallowing function using the Fiberoptic Endoscopic Evaluation of Swallowing (FEES). The results were statistically analyzed and correlated with demographic and MS-related parameters. RESULTS: Of the 304 people with RRMS enrolled in the study, 46 (15.1 %) reported having subjective difficulty swallowing when asked a simple question. The DYMUS questionnaire was positive in 59 (19.4 %) of the 304 patients; 51 (16.8 %) had an abnormality on the TWST. A clear correlation (r = 0.351, p < 0.01) was found between the DYMUS and TWST results, but a significant proportion of patients (about half) had an abnormality on only one of these tests. The positivity of at least one of the screening methods used (DYMUS or TWST) had a better chance of identifying a patient with dysphagia than a simple question (p < 0.001). Of the patients with a positive result for difficulty swallowing, 37 underwent FEES, which confirmed dysphagia in 94.6% of this subgroup. Patients with higher Expanded Disability Status Scale (EDSS) scores, female gender, and older age were at higher risk of developing dysphagia. CONCLUSION: The DYMUS questionnaire and TWST had a confirmed potential to identify more patients with dysphagia than a simple question about swallowing problems. However, our study found only a partial overlap between DYMUS and TWST; a combination of these two methods was more sensitive in identifying patients with MS at risk of dysphagia. Furthermore, the screening showed excellent specificity: almost 95 % of the positively screened patients had dysphagia confirmed by objective methods. Age, female gender, and a higher EDSS score appear to be potential risk factors for dysphagia in patients with MS.
Keywords: ženské pohlaví; Female; Multiple Sclerosis, Relapsing-Remitting; roztroušená skleróza; průzkumy a dotazníky; relabující-remitující roztroušená skleróza; lidé; Deglutition; Deglutition Disorders; polykání; Humans; Surveys and Questionnaires; Multiple Sclerosis; poruchy polykání